Sociocultural processes of transformation modern music education in Ukraine - Loshkov, Yurii (Professional Art Education, 2021)
The purpose of the article is to transformational processes in modern music education in Ukraine. Author certain that ideological basis of professional musical art of European type is understanding of music as facilities of moral education, on the basis of comprehension what musical education was formed. Methods & methodology. The article has a set of methods typical for historical and pedagogical studies: historical, semiotic, contextual, typological. Results. It is well-proven that the system of the educational and sociocultural establishments called to provide functioning of musical culture in modern Ukraine was folded on the basis of aesthetics of academic musical art. Transformation processes are educed in the areas of musical formation of Ukraine, conditioned by social and cultural changes. Consequently, transformations in musical formation industry of Ukraine are predefined by social and cultural processes as calls to ideological foundation of academic musical art. Social changes cause transformations of different levels, which cannot be clearly estimated by contemporaries. Thus, cultivation of new musical specializations can be examined, from the one side, as a way of academic of certain unacademic directions; and from the other side, as deacademic beginning of musical education. The questions raise about the discrepancy between the content of academic music education and the realities of modern representative practice, point about the need to modernize the content components in order to increase the competitiveness of the graduate - a professional musician of the educational system. Conclusions. The system level transformations cannot be perceived simply. In this context consciously influence and regulate transformation processes are possible in condition of formulation the weighted long-term cultural politics by government, and consequently understanding of place and role of musical art in Ukrainian society.